2022
DOI: 10.1039/d1gc04512a
|View full text |Cite
|
Sign up to set email alerts
|

Sequential resolution of (S) and (R)-6-fluoro-chroman-2-carboxylic acid by two esterases in turn

Abstract: Optically pure 6-fluoro-chroman-2-carboxylic acids (FCCAs), including (S) and (R)- configuration, are pivotal chiral building blocks in the pharmaceutical industry. To date, the production of (S) and (R)-FCCA mainly depends on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…388 Various biocatalytic methods for the synthesis of carboxylic acids have been developed, complementing nonenzymatic approaches. 389 These methods include the hydrolysis of nitriles by nitrilases, 390−392 the conversion of aldehydes by hydroxynitrile lyases with subsequent hydrolysis, 393 the hydrolysis of esters by esterases, 394 and the oxidation of alcohols or aldehydes by dehydrogenases and oxidases. 395 Glieder et al reported a hydroxynitrile lyase mutant from Prunus amygdalus for the enantioselective synthesis of α-hydroxyacids by the addition of HCN to aldehydes and the subsequent hydrolysis of the intermediately formed cyanohydrins.…”
Section: Chromo-and Fluorogenic Probes For Carboxylic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…388 Various biocatalytic methods for the synthesis of carboxylic acids have been developed, complementing nonenzymatic approaches. 389 These methods include the hydrolysis of nitriles by nitrilases, 390−392 the conversion of aldehydes by hydroxynitrile lyases with subsequent hydrolysis, 393 the hydrolysis of esters by esterases, 394 and the oxidation of alcohols or aldehydes by dehydrogenases and oxidases. 395 Glieder et al reported a hydroxynitrile lyase mutant from Prunus amygdalus for the enantioselective synthesis of α-hydroxyacids by the addition of HCN to aldehydes and the subsequent hydrolysis of the intermediately formed cyanohydrins.…”
Section: Chromo-and Fluorogenic Probes For Carboxylic Acidsmentioning
confidence: 99%
“…Various biocatalytic methods for the synthesis of carboxylic acids have been developed, complementing nonenzymatic approaches . These methods include the hydrolysis of nitriles by nitrilases, the conversion of aldehydes by hydroxynitrile lyases with subsequent hydrolysis, the hydrolysis of esters by esterases, and the oxidation of alcohols or aldehydes by dehydrogenases and oxidases …”
Section: Chromo- and Fluorogenic Probes For Carboxylic Acidsmentioning
confidence: 99%